Improving E-Book Learning Experience by Learning Recommendation - Fergyanto E. Gunawan; Benfano Soewito; Sevenpri Candra (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Technology  Enhanced Learning  is one of the  most dynamic   areas   of  inquiry   in  education.   One  form  of  TELs, that  is on-screen  learning,  has  become  the  topic  of interest  of many  works.  It  is  popular mainly  with  young  people  despite all  ﬁndings,  which  undoubtedly suggest  that  it  is  detrimental to  learning.   The  method   hinders   learning   experience   due  to the reading spatial  instability,  difﬁculties  in establishing  mental map,  and  poor  visual  ergonomics.  Currently, many  textbooks are available  in electronic form and a majority of the students  in Bina  Nusantara University  in Indonesia,  for  example,  consider the form to be more convenient  and preferable. In the electronic form,  the  textbooks  are  much  more  affordable.  They  can  be obtained  easier  than  the  printed books.  This  work  intends  to explore   a  method   of  improving   the  learning   quality   of  the electronic textbooks. The improvement is expected to be achieved by  enriching   the  electronic   textbook   with  cues  in  the  form of margin  notes, highlights, markers, lines and arrows,  and navigation  tools provided  by the subject  matter expert.  The idea is implemented on  a  class at  the  university  and  its  effects are assessed.  The  participants are  divided  into  two  groups  having the  same  distribution of the  past  academic  performance where one group  is assigned to learn  using the recommendation system and  the  other  is without  the  system.  After  the  learning,  their understandings are assessed systematically by qualitative  and quantitative methods. The participants with the recommendation system outperform those without  signiﬁcantly,  which is marked by the values of the Cohen’s  effect size d larger  than  1.20 with the standard deviation  about  0.563.